Nadzri Morshidi - baju kurung / Norazreen Mat Raius … [et al.] - MAT RAIUS, NORAZREEN; HASSAN BASRI, NORFARAHANA JASMIN; PEET, SHAHROLNIZAM; ABDULLAH, SITI HARLIZA; ISMAIL @ MUSTAPHA, SITI SHARIFAH NUR (2020)
This report is focus on a case study of the business Nadzri Morshidi who is designer and online seller of Baju Kurung. His business is located at R-02-16, Emira Residence & Retails Jalan Akuatik A13/64A Section 13, 40100 Shah Alam, Selangor. For this purpose, we had an interview session with the owner about the business information and SWOT analysis to put in our case study report. Learning the current condition about the Strength, Weakness, Opportunity and Threats can help to develop strategies in the business. Findings and discussion also important tools for better planning and it's a kind of brainstorming to make a success business in the future.